Maori Disputes and Their Resolution - Quince, Khylee (Dispute resolution in New Zealand, 2007)
http://librarysearch.auckland.ac.nz/primo_library/libweb/action/display.do?fn=search&doc=uoa_voyager1760462&vid=UOA2_A
Keywords: crown law; rangatiratanga; tikanga | indigenous law